Pendidikan Multikultural Dalam Perspektif Pendidikan Islam - Harahap, Andika Septio; Swanto, Yola Anjeli; Winda, Winda; Arif, Muhammad (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2023)
The results of this study explain several aspects regarding multicultural education in the perspective of Islamic education. This research is a qualitative descriptive research. Collecting data is by using literature study techniques, namely data collected by going through several stages of review originating from books, notes, literature and various reports related to the problem to be solved from various sources both from journals and books. The results of this study indicate the aspects discussed in multicultural education in an Islamic perspective consisting of: (1) the notion of multiculturalism, this multiculturalism, is an ideology which places more emphasis on equality in cultural diversity, (2) the principle of multicultural education, in principle Multicultural education is education that gives respect to diversity, (3) multicultural characteristics in an Islamic view, the characteristics of multicultural education in an Islamic education perspective can be identified through seven components, namely studying life in society with differences that occur in an idea or we call it a concept ( ideology), respecting three mutual aspects (understanding, respect, and mutual trust), having openness in thinking, appreciating and so on, (4) the purpose of multicultural education, multicultural education aims to form individuals who have understanding, appreciation, and skills in dealing with diversity culture, religion, and ethnic background that exist in society. ABSTRAKHasil penelitian ini menjelaskan beberapa aspek-aspek berkenaan dengan pendidikan multikultural dalam perspektif pendidikan Islam. Penelitian ini berjenis penelitian deskriptif kualitatif. Mengumpulkan data adalah dengan memakai teknik studi kepustakaan, yaitu data dikumpulkan dengan melalui beberapa tahap telaah yang berasal dari buku, catatan, literature dan berbagai laporan terkait masalah yang akan dipecahkan dari berbagai sumber baik dari jurnal dan buku-buku. Hasil penelitian ini menunjukkan aspek-aspek yang dibahas pada pendidikan multikultural dalam perspektif Islam yang terdiri dari : (1) pengertian multikultural, multikulturalisme ini, merupakan sebuah ideologi yang dimana lebih menekankan pada kesetaraan dalam keragaman budaya, (2) prinsip pendidikan multikultural, secara prinsip pendidikan multikultural adalah pendidikan yang memberikan penghargaan terhadap keragaman, (3) karakteristik multikultural dalam pandangan Islam, karakteristik pendidikan multikultural dalam perspektif pendidikan Islam dapat diidentifikasi melalui tujuh komponen, yaitu mempelajari kehidupan dalam masyarakat dengan perbedaan yang terjadi pada sebuah gagasan atau kita sebut sebagai konsep (ideologi), menghormati tiga aspek mutual (pengertian, penghargaan, dan saling yakin), memiliki keterbukaan dalam berpikir, mengapresiasi dan sebagainya, (4) tujuan pendidikan multikultural, pendidikan multikultural bertujuan untuk membentuk individu yang memiliki pemahaman, penghargaan, dan keterampilan dalam menghadapi keragaman budaya, agama, dan latar belakang etnis yang ada dalam masyarakat.